Calculation of a steel prestressed truss with a span of 60 m, taking into account seismic impacts (Международный научный журнал «Инженер», 2026)
In this paper, calculations of a steel roof truss with prestressed puffs with a span of 60 m are presented. The calculations were performed in a geometrically nonlinear formulation in the LIRA CAD 2022 software package. The method of "engineering nonlinearity" was used to account for the vertical seismic load. It shows a significant increase in the rigidity of the truss and significant savings in steel due to the use of high-strength puffs.